POTENTIAL USE OF BUFFALO SKIN AS A RAW MATERIAL FOR LEATHER TANNING INDUSTRY IN INDONESIA - Said, Muhammad Irfan; Hifizah, Amriana (Proceeding Buffalo International Conference, 2013)
One of the problems faced by the leather industry and leather goods industry in Indonesia is availability of raw materials. While the demand from various countries for goods made of leather is increasing, the ability of the domestic leather industry to provide the products are still very low due to insufficient supply of raw materials. So far, the raw materials for leather industry are dominated by cow, goat, or sheep leather, while the raw material of buffalo skin is still very limited. As buffalo population in Indonesia is low, the use of buffalo skin as raw material for leather industry is limited. The characteristics of buffalo leather are similar to those of cow leather, therefore buffalo leather has potential to support the supply of raw materials for the leather industry. The final quality of the buffalo skin is determined by the buffalo population in the upstream sector, which should be in line with the improvement of production, feeding, and health management on farm sector, as well as cutting techniques, pickling, and tanning in the downstream sector.